2020
DOI: 10.1186/s12916-020-01730-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal lipid profile in early pregnancy is associated with foetal growth and the risk of a child born large-for-gestational age: a population-based prospective cohort study

Abstract: Background Lipids such as cholesterol and triglycerides play an important role in both maternal and foetal energy metabolism. Little is known about maternal lipid levels in pregnancy and their effect on foetal growth. The aim of this study was to assess maternal lipid levels, foetal growth and the risk of small-for-gestational age (SGA) and large-for-gestational age (LGA). Methods We included 5702 women from the Generation R Study, a prospective population-based cohort. Maternal lipid levels (total cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 71 publications
6
41
0
Order By: Relevance
“…The findings were not explained by maternal BMI, suggesting effects of maternal cholesterol and triglyceride concentrations within the normal range were independent of BMI. In line with our findings, results from the same study cohort also showed that maternal triglyceride and cholesterol levels are associated with increased fetal growth rates which resulted in a higher birth weight [40]. These findings might suggest that these increased maternal lipid levels have consequences for fetal cardiac development and might lead to persistent subclinical consequences in childhood.…”
Section: Maternal Weight Gain During Pregnancysupporting
confidence: 90%
“…The findings were not explained by maternal BMI, suggesting effects of maternal cholesterol and triglyceride concentrations within the normal range were independent of BMI. In line with our findings, results from the same study cohort also showed that maternal triglyceride and cholesterol levels are associated with increased fetal growth rates which resulted in a higher birth weight [40]. These findings might suggest that these increased maternal lipid levels have consequences for fetal cardiac development and might lead to persistent subclinical consequences in childhood.…”
Section: Maternal Weight Gain During Pregnancysupporting
confidence: 90%
“…Under normal physiological conditions, over the duration of a pregnancy there is a visible increase in lipid concentrations, including in TG and CHL [ 44 ]. Adank et al [ 45 ] conducted a study on pregnant women and found a correlation between the concentrations of TG and remnant cholesterol in early pregnancy and increased fetal body weight and risk of having large for gestational age (LGA) infants. It has been shown in mice that circulating TG, HDL, and total CHL are increased by the gut microbiota under conditions of a high-fat diet [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study by Adank et al. [ 28 ] with 5702 pregnant women showed that early pregnancy TG level was associated with slight increase of risk of large-for-gestational age (LGA) (OR: 1.18, 95% CI: 1.07–1.29). Although maternal circulating TG does not directly cross the placenta, the presence of lipoprotein receptors, fatty acid–binding proteins, and different lipase activities in the placenta enable efficient transfer of maternal fatty acids to the foetus [ 29 ].…”
Section: Discussionmentioning
confidence: 99%